Value relevance of accounting information and implication on stock price movement: empirical evidence from listed bank finance and insurance companies in sri lanka - Nimalatheepan, S. (University of Jaffna, 2016)
The investigation of value relevance of accounting information and its implication for emerging markets have received dearth attention in the literature. This study evaluates the relation between the value relevance of accounting information and stock price movement, using data obtained from 20 listed Bank Finance and Insurance companies in Sri Lanka covering the period of 6 years from 2009 to 2014. In order to select the sample random, sampling method used. The research design of this study based on a quantitative approach and analysis secondary data. Data of the selected firms which are listed in the Colombo stock exchange (CSE) Sri Lanka were obtained from their websites. This study identifies value relevance of accounting information by three separate financial ratios: Earning per Share (EPS), Return on Equity (ROE) and Earning Yield (EY) as independent variable while market price per share (MPS) as a dependent variable of this study. The statistical tests were used includes: descriptive statistics, correlation and regression analyses. Through the multiple correlation analysis with the help of user friendly statistical software it is found, there is significant and positive association between MPS and EPS (P= 0.000, < 0.01). Which indicate that, as the EPS increases it would tend to increase the MPS of the company. On the other hand, there is significant and negative correlation between MPS and EY (P=0.045, < 0.05). Which indicate that, as the EY increases it would tend to reduce the MPS of the company. The study also illustrates that main accounting information proxies have strong predict powers on variations of market share price.
Keywords: Accounting information; Colombo stock exchange; Earning per share; Earning yield; Market price per share; Return on equity; Value relevance